2018
DOI: 10.1159/000484653
|View full text |Cite
|
Sign up to set email alerts
|

Primary Liver Diffuse Large B-Cell Lymphoma following Complete Response for Hepatitis C Infection after Direct Antiviral Therapy

Abstract: Introduction: Hepatitis C infection is highly prevalent worldwide and has a well-known association with B-cell lymphoid malignancies. Antiviral therapy has successfully decreased the rate of liver cirrhosis and improved the outcome in patients with hepatitis C-associated lymphomas. However, although there are a few case reports of aggressive lymphomas after successful hepatitis C therapy, the mechanism behind this association remains unclear. Case Presentation: We present the case of a 55-year-old man with chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Moreover, acute or chronic HCV infections are known to be associated with increased frequencies of BCL-6 and p53 gene mutations in B-cells in vitro ; mutations in these genes have been linked to DLBCL ( 31 ). Accordingly, HCV-related lymphomagenesis may be attributed to either chronic viral antigen stimulation or genetic mutations that lead to the clonal expansion and malignant transformation of B-cells, as previously reported ( 7 , 5 , 25 ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, acute or chronic HCV infections are known to be associated with increased frequencies of BCL-6 and p53 gene mutations in B-cells in vitro ; mutations in these genes have been linked to DLBCL ( 31 ). Accordingly, HCV-related lymphomagenesis may be attributed to either chronic viral antigen stimulation or genetic mutations that lead to the clonal expansion and malignant transformation of B-cells, as previously reported ( 7 , 5 , 25 ).…”
Section: Discussionmentioning
confidence: 55%
“…However, several possible mechanisms have been proposed in recent publications. Andrade et al ( 25 ) suggested that HCV-induced genetic damage produced a survival signal in B-cells, which may lead to late transformation, even years after successful HCV therapy. Indeed, genetic mutations derived from either acute or chronic HCV infection are known to persist, even after HCV clearance ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are even few available data on PHL occurring after DAA therapy, and to the best of our knowledge, there are only two cases reporting this association in the literature. 1 2 The issues raised about HCC following DAA therapy, which led to an avalanche of studies with contradictory findings, make these anecdotal observations more disquieting.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the development of lymphoma occurs in the context of clearance of chronic HCV infection. There are few reports [17,18] to support the development of HCV-associated B-cell lymphoma after clearance of HCV viral load. Andrade et al [17] hypothesize that HCV clearance may restore host T-cell and B-cell mediated immunity facilitating a previously suppressed lymphoid malignant clone to proliferate.…”
Section: Discussionmentioning
confidence: 99%